TERMITES ENDANGERED TRADITIONAL MEDICAL PLANTS - Syaukani Syaukani (Jurnal Natural, 2013)
Surveys on traditional medical plants affected by termites have been conducted since June to August 2010 at Ketambe, northern Aceh. Traditional medical plants and their natural habitats were obtained through interviewing local people. Termites were collected by adopted a Standardized Sampling Protocol and final. taxonomic confirmation was done with the help of Termite Research Group (the Natural History Museum, London). About 20 species of medical plants were attacked by termites with various levels. Nine genera and 20 species were collected from various habitats throughout Ketambe, Simpur as well as Gunung Setan villages. Coffe (Coffea arabica), hazelnut (Aleurites moluccana) , and areca (Area catechu) were among the worse of traditional medical  plant that had been attached by the termites.